Nutrition Relieving Strategies to Relieve Negative Effect of Heat Stress on Livestock and Poultry - Jing, Yanrong; Luo, Caiyu; Zhu, Rongxia; Zuo, Zecheng; Feng, Xin (Syiah Kuala University, 2025)
Heat stress induces systemic inflammatory responses that severely compromise the growth and health of livestock and poultry. Gradual climate change poses escalating threats to the economic viability of animal husbandry through increasingly frequent extreme heat events. Under thermal stress, persistent inflammation in muscles and tissues disrupts metabolic processes, impairing muscle growth and fat deposition, which translates to reduced yield and quality in farmed animals. Understanding the mechanisms of heat stress-induced inflammation facilitates the implications of intervention strategies. This review synthesizes characteristic changes in key biochemical indicators triggered by heat stress and reviews nutritional strategies aimed at restoring normal physiological parameters, thereby providing references for mitigating heat stress in livestock and poultry and ultimately enhancing productivity and economic sustainability.